ANALISIS TINGKAT PENGANGGURAN TERBUKA DI PROVINSI YOGYAKARTA TAHUN 2015-2025 - Awali Fadhil Aryanto; Dwi Yando Saputra; Sri Ningsih (PT. Hasba Edukasi Mandiri, 2026)
This study is motivated by the dynamics of the Open Unemployment Rate (OUR) in the Special Region of Yogyakarta, which exhibits fluctuating patterns and is influenced by changes in economic conditions both before, during, and after the COVID-19 pandemic. This study aims to analyze the development of the OUR for the 2015–2025 period and identify the factors influencing it, such as education, labor force structure, and economic growth. The method used is quantitative descriptive analysis utilizing secondary data from the Central Statistics Agency (BPS) through documentation techniques. The analysis was conducted using a time series approach and supported by line graph visualizations to clarify the patterns of change in the TPT. The results indicate that the TPT in DIY declined during the 2015–2019 period, surged sharply during the 2020–2021 pandemic, and gradually declined again during the 2022–2025 recovery period. However, this decline does not fully reflect an improvement in labor market quality, as there remains educated unemployment and a dominance of the informal sector. The uniqueness of this study lies in the integration of long-term trend analysis with a structural approach to the labor market at the regional level. The implications of the study highlight the need for policies that focus not only on economic growth but also on improving the quality of human resources and aligning education with labor market needs.